Congenital Myenteric Hypoganglionosis. (August 2021) - Kapur, Raj P.; Bellizzi, Andrew M.; Bond, Steffan; Chen, Haiying; Han, Jeong S.; LeGallo, Robin D.; Midgen, Craig; Poulin, Alysa A.; Uddin, Naseem; Warren, Mikako; Velázquez Vega, José E.; Zuppan, Craig W.
Abstract : Congenital myenteric hypoganglionosis is a rare developmental disorder characterized clinically by severe and persistent neonatal intestinal pseudoobstruction. The diagnosis is established by the prevalence of small myenteric ganglia composed of closely spaced ganglion cells with sparse surrounding neuropil. In practice, the diagnosis entails familiarity with the normal appearance of myenteric ganglia in young infants and the ability to confidently recognize significant deviations in ganglion size and morphology. We review clinical, histologic, and immunohistochemical findings from 12 patients with congenital myenteric hypoganglionosis in comparison with similar data from age-matched controls and clearly delineate the diagnostic features of the condition. Practical guidelines are provided to assist surgical pathologists, who are likely to encounter this condition only infrequently. The diagnosis typically requires full-thickness intestinal biopsy as the abnormality is confined to the myenteric plexus in many patients. Immunohistochemistry for Hu C/D may be used to confirm hypoganglionosis. Reduced staining for calretinin and NeuN implicates a selective deficiency of intrinsic primary afferent neurons in this disease. Abstract : Supplemental Digital Content is available in the text.